Transarterial Chemoembolization in Patients with Hepatocellular Carcinoma: Predictors of Survival - Summit Sawhney; Aldo J Montano-Loza; Peter Salat; Mairin McCarthy; Norman Kneteman; Judith Meza-Junco; Richard Owen (Canadian Journal of Gastroenterology)
BACKGROUND: Transarterial chemoembolization (TACE) is the mainstay of management for patients with hepatocellular carcinoma who are not suitable for curative treatments.